LASER THERAPY IN THE COMPLEX TREATMENT OF PATIENTS WITH PERIODONTAL TISSUE DISEASES - Sherboyeva Muqadamkhon Husanboevna (Scientific Trends, 2023)
Application high-intensity and low-intensity laser therapy in complex treatment of chronic marginal periodontitis has been studied. In USMA dental clinic stomatologic investigation and treatment of 52 patients has been carried. Clinical research throughout 3 months of supervision has proved efficiency of application of methods of laser therapy in complex treatment of periodontal diseases.
Keywords: marginal periodontitis, laser, intensity.